Bicyclists' visual strategies when conducting self-paced vs. system-paced smartphone tasks in traffic. (August 2016) - Ahlstrom, Christer; Kircher, Katja; Thorslund, Birgitta; Adell, Emeli
Highlights: Cyclists use visual strategies when interacting with mobile phones while cycling. Self-paced tasks have longer mean and maximum glance durations than system-paced tasks. Cyclists prepare for self-initiated tasks by for example choosing a suitable location. Internet browsing causes longer glance durations and numbers compared to call and sms. Cyclists use spare capacity to handle glances towards the phone. Abstract: Visual distraction among cyclists interacting with their mobile phones is a growing concern. Yet, very little research has actually investigated how cyclists apply visual strategies and adapt task execution depending on the traffic situation. The aim of this study is to investigate visual behaviour of cyclists when conducting self-paced (initiated by the cyclist) vs. system-paced (initiated by somebody else) smartphone tasks in traffic. Twenty-two cyclists completed a track in real traffic while listening to music, receiving and making calls, receiving and sending text messages, and searching for information on the internet. The route and the types of tasks were controlled, but the cyclists could choose rather freely when and where along the route to carry out the tasks, thus providing semi-naturalistic data on compensatory behaviour. The results show that the baseline and music conditions were similar in terms of visual behaviour. When interacting with the phone, it was found that glances towards the phone mostly came at the expense of glances towards traffic irrelevant gaze targets and also led to shortened glance durations to traffic relevant gaze targets, while maintaining the number of glances. This indicates that visual "spare capacity" is used for the execution of the telephone tasks. The task type influenced the overall task duration and the overall glance intensity towards the phone, but not the mean nor maximum duration of individual glances. Task pacing was the factor that influenced visual behaviour the most, with longer mean and maximum glance durations for self-paced tasks. In conclusion, the cyclists used visual strategies to integrate the handling of mobile phones into their cycling behaviour. Glances directed towards the phone did not lead to traffic relevant gaze targets being missed. In system-paced scenarios, the cyclists checked the traffic more frequently and intensively than in self-paced tasks. This leads to the assumption that cyclists prepare for self-initiated tasks by for example choosing a suitable location. Future research should investigate whether these strategies also exists amongst drivers and other road user groups.